2020
DOI: 10.1016/j.ajps.2020.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from small molecule to nano-drug delivery systems: An emerging approach for cancer therapy of ursolic acid

Abstract: Ursolic acid (UA), a natural pentacyclic triterpenoid, possesses widespread biological and pharmacological activities. However, drawbacks such as low bioavailability, poor targeting and rapid metabolism greatly hinder its further clinical application. Recently, with the development of nanotechnology, various UA nanosystems have emerged as promising strategies for effective cancer therapy. This article reviews various types of UA-based nano-delivery systems, primarily with emphasis placed on novel UA-based carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 128 publications
0
31
0
Order By: Relevance
“…The poor solubility of compounds translates into a short half-life in blood circulation, low bioavailability, and the insufficient effectiveness of therapy [ 25 , 26 ]. On the other hand, after intravenous administration, the low-molecular-weight triterpenoids can undergo non-specific distribution in the body [ 27 ]. Pharmacological effects may be enhanced by the development of novel drug delivery systems (DDSs) based on nanocarriers.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor solubility of compounds translates into a short half-life in blood circulation, low bioavailability, and the insufficient effectiveness of therapy [ 25 , 26 ]. On the other hand, after intravenous administration, the low-molecular-weight triterpenoids can undergo non-specific distribution in the body [ 27 ]. Pharmacological effects may be enhanced by the development of novel drug delivery systems (DDSs) based on nanocarriers.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…Despite the continuous development and undeniable overall benefits of the modern nanoformulations used in DDSs, there are still many unknowns and challenges that limit their widespread use. The current challenges for scientists in designing and manufacturing nanoformulations are related to (i) the properties of the used biomaterials, (ii) production limitations, (iii) loading capacity, (iv) stability, (v) toxicity, and (vi) biological barriers [ 27 , 30 , 48 ]. The properties of biomaterials, like charge of surface group or biodegradability, can affect their cytotoxicity, biocompatibility, and membrane permeability [ 29 ].…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…Recently, traditional Chinese medicine, especially involving natural products, has attracted increasing attention as antitumor therapy. Ursolic acid (UA), a pentacyclic triterpenoid, can be isolated from various natural sources, such as Salvia officinalis , Rosmarinus officinalis , and Sanguisorba officinalis (Shao et al., 2020 ). It has been reported that UA has various pharmacological properties, including antitumor, anti-inflammatory, antibacterial, and antioxidant effects (Mlala et al., 2019 ; Shao et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ursolic acid (UA), a pentacyclic triterpenoid, can be isolated from various natural sources, such as Salvia officinalis , Rosmarinus officinalis , and Sanguisorba officinalis (Shao et al., 2020 ). It has been reported that UA has various pharmacological properties, including antitumor, anti-inflammatory, antibacterial, and antioxidant effects (Mlala et al., 2019 ; Shao et al., 2020 ). Previous studies have shown that UA can significantly inhibit proliferation and induce apoptosis of different types of malignant tumor cells, including those of breast cancer, hepatocarcinoma, and gastric cancer (Zhang et al., 2013 , 2016a ; Liu et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer [167], breast cancer [168], prostate cancer, lung cancer, hepatocellular carcinoma [169], gall bladder carcinoma, melanoma [170] Gold-ursolic acid into PLGA NP, long-circulating and pH-sensitive liposomes [171], PEG modified liposome [172], ursolic acid-loaded chitosan NP [173], pH-sensitive mesoporous silica NP CD, cyclodextrin; NP, nanoparticle; PCL, polycaprolactone; PEG, polyethylene glycol; PLA, poly(lactide); PLGA, poly lactic-co-glycolic acid; PVP, poly(vinyl pyrrolidone); QD, quantum dot; SLN, solid lipid NP; TPGS, tocopheryl polyethylene glycol 1000 succinate.…”
Section: Ursolic Acidmentioning
confidence: 99%